A Thematic Analysis of Career Adaptability in Retirees Who Return to Work - Luke, Jennifer; McIlveen, Peter; Perera, Harsha N. (Frontiers in Psychology, 2016)
Retirement can no longer be conceptualized as disengagement, as the end of a person’s career, as it is in the life-span, life-space theory. Increasingly, retirees are returning to work, in paid and unpaid positions, in a part-time or full-time capacity, as an act of re-engagement. Vocational psychology theories are yet to adequately conceptualize the phenomenon of retirees’ re-engagement in work. The research reported in this paper is the first attempt to understand re-engagement through the theoretical lens of career construction theory and its central construct, career adaptability. The study involved intensive interviews with 22 retirees between the ages of 56 and 78 years (M = 68.24), who had retired no less than one year prior to the study. Participants were engaged in a discussion about their reasons for returning to the world of work. Thematic analysis of interview transcripts extracted evidence of the four career adaptability resources: concern, control, curiosity, and confidence. In addition, the influence of family and making a contribution were discerned as important themes. These findings are the first evidence that the career construction theory and career adaptability provide a new conceptual lens to theorize and conduct research into the phenomenon of retirement.